An Empirical Analysis of the Voluntary Disclosure Practices of Unired Arab Emirates Listed Companies in an International Financial Reporting Standards Environment - THOMAS, Suja Sarah; AHMED, Ibrahim Elsiddig (Journal of Advanced Research in Management, 2018)
This study explores the voluntary disclosure practices of UAE listed companies in the current IFRS environment and compares them with international best practices as revealed by extant literature. For the purpose of the study a voluntary disclosure checklist was designed. The checklist was based on instruments used extensively in mature markets and tailored to the needs of an ‘emerging’ market economy in view of the vulnerability of emerging market stocks to extensive disclosures. An important reference point is that IFRS disclosures requirements are periodically revised. Hence, disclosures that have now become ‘statutory’ under IFRS reporting have not been included in the checklist. Data were collected by empirically examining the annual reports of listed companies in the UAE stock markets over a five year period, 2010 to 2014, and analyzed statistically to derive significant relationships. It is clear that legal requirements shape much of the disclosure practices in the UAE markets. Results of the analysis showed that large companies especially in the financial services sector score high on the voluntary disclosure index. The overall index falls in the range of 10 to 30. Other companies including SMEs have also begun to realize the benefits of transparency in financial reporting.